Promoting students' tolerance awareness in the context of peace education through Wayang Golek - Harjianto, Feri Henri; Handarini, Dany Moenindyah; Setiyowati, Arbin Janu (Universitas Negeri Yogyakarta, 2021)
Tolerance awareness is one of important aspect to realizing peace education that train students to avoid of using violence. This study aims to represent the results of the tolerance awareness training guide using